Multicolor AIE polymeric nanoparticles prepared via miniemulsion polymerization for inkjet printing. (June 2020) - Liang, Xiaoqin; Tao, Meng; Wu, Die; Yu, Bang; Mi, Yifang; Cao, Zhihai; Zhao, Zujin; Chen, Dongzhi
Abstract: Owing to the strong solid-state luminescence of aggregation-induced emission luminogen (AIEgen), polymer/AIEgen nanoparticles (NPs) have great potential in application as high-quality luminescent inks. In this work, polymer/AIEgen NPs with a particle size below 70 nm were efficiently prepared through encapsulation of AIEgens with various colors within polymeric matrix via miniemulsion polymerization. The prepared polymer/AIEgen NPs emitted bright and stable blue, green, or orange-red fluorescence. The polymer/AIEgen NP inks suitable for inkjet printing were conveniently made through addition of a non-ionic surfactant to the emulsions with corresponding polymer/AIEgen NPs. The bright, high-resolution, and UV-responsive images were printed on cotton textiles with polymer/AIEgen NP inks. The microscopic observation indicated that the polymer/AIEgen NPs could form homogenous films onto the cotton fibers. More promisingly, the prepared polymer/AIEgen NPs with various colors had good compatibility, and they could be directly mixed to prepare multicolor polymer/AIEgen NP inks for handwriting. Graphical abstract: Multicolor AIE polymeric nanoparticles with various colors are efficiently prepared through encapsulation of AIEgen via miniemulsion polymerization, and were applied for inkjet printing and handwriting. Image 1 Highlights: Multicolor AIE polymeric NPs for inkjet printing are prepared via miniemulsion polymerization. The AIE polymeric NP inks are made by simple addition of a nonionic surfactant to the initial emulsions. The printed images on the cotton textiles display a bright and high-quality fluorescence under UV light.